Upaya pencegahan yang dilakukan oleh dokter gigi di Makassar terhadap bahaya akibat penggunaan amalgam Prevention of dentists in Makassar to the risk of amalgam - Sarwo Edy; Rasmidar Samad (DiscoverSys Inc., 2012)
Makassar is a big city with the highest number of dentists in South Sulawesi. Currently there are many dentists in thecity of Makassar using amalgam as a filling material for cheaper and more durable, so it is preferred by patients.Generally, they have ignored the dangers of exposure to mercury in amalgam through breathing or skin contact. For itwas on this descriptive observational study noted the efforts of Makassar dentist to prevent hazards due to the use ofamalgam in practice. From the general population of dentists who were registered as members of the IndonesianDentists Association (IDA) branch Makassar as much as 258 people, based on the opinions of Gay and Diehl withanticipation drop out of 20%, was obtained a sample of 100 people, but only 67 respondents (male = 13, female = 54)uses amalgam. The results are efforts to prevent the danger of amalgam achieved 51-75% by 32 respondents (47.7%),76-100% by 25 respondents (37.3%), 26-50% by 10 respondents (15%), and no respondents who seek prevention ofcross infection hazard to the achievement of 0-25%. Efforts to prevent with the achievement of 51-75% (32respondents) and 76-100% (25 respondents), could be said to have met the standard, concluded that 85% of dentists inMakassar have good enough prevention efforts to amalgam while doing their practice.